Poetyckie marzenie Tadeusza Gajcego w konfrontacji z tradycją romantyczną i oceną pokolenia Kolumbów przez Czesława Miłosza i Zbigniewa Herberta = The poetic dream of Tadeusz Gajcy confronted with the romantic tradition and evaluation of the attitude of the Generation of Columbuses by Czesław Miłosz and Zbigniew Herbert - Brasse, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The poetic dream of Tadeusz Gajcy was not only a means of overcoming the horror and absurdity of the times, but also a way of expressing his personal relationship to the concept of death and sacrifice - growing, after all, out of the experiences of everyday occupation. This subject dominated the creative consciousness of Gajcy and had a decisive influence on the nature of the message contained in his testa - mental Grom powszedni.
Keywords: poetyckie marzenie; Gajcy, Tadeusz Stefan (1922-1944); romantyczna tradycja; pokolenie Kolumbów; Miłosz, Czesław (1911-2004); poetic dream; Romantic tradition; Generation of Columbus